Experimental and computational analysis of acoustic characteristics of warp-knitted spacer fabrics. Issue 4 (2nd April 2020) - Abedkarimi, Razieh; Hasani, Hossein; Soltani, Parham; Talebi, Zahra
Abstract: As a kind of porous medium, textiles have recently received increased attention for acoustic applications due to their high profitability and low cost and environmental impact. 3D knitted spacer fabrics stand out as a unique class of textile materials. These materials simultaneously are soft, voluminous and highly porous and therefore are expected to be suitable for sound absorbing applications. This article aims to investigate the acoustic performance of 3D warp-knitted spacer fabrics. To this end, acoustic behavior of warp-knitted spacer fabrics was experimentally measured using the impedance tube method. In order to predict the sound absorption behavior of fabrics, a simple geometrical model was created. Flow resistivity was calculated by numerically solving incompressible laminar Newtonian flow through the 3D pore space of generated structure. The frequency-dependent sound absorption coefficient of the warp-knitted spacer fabric was predicted using the empirical models of Delany and Bazley, Garai and Pompoli and Dunn and Davern. The results showed that the Dunn and Davern model can predict sound absorption characteristics of warp-knitted spacer fabrics in the mid-to high-frequency ranges. At low frequency ranges; however, none of the empirical models can reasonably predict sound absorption behavior of the fabrics.